Proses Redistribusi Kebutuhan Guru Guna Meningkatkan Mutu Pembelajaran di SMPN 16 Surabaya - Afrizal Rayhan Alfin Maulana; Allif Afifah Aulia; Aulia Nurisma A’yunina; Syunu Trihantoyo; Nuphanudin (Pusat Riset dan Inovasi Nasional, 2024)
This research reveals the process of redistributing teachers' needs at SMPN 16 Surabaya, highlighting its impact on the quality of learning experiences. This research utilizing a qualitative descriptive approach, the research centers on the school environment as the focus of teacher redistribution. Primary data were gleaned from in-depth interviews, focused group discussions, and participant observations, while secondary data were garnered through document analysis, including school records and educational policies. The research outcomes offer valuable perspectives for education administrators, policymakers, and researchers, suggesting the potential implementation of efficacious practices for continuous enhancement in SMPN 16 Surabaya and analogous educational institutions.